Herring Oil and Omega Fatty Acids Inhibit Staphylococcus aureus Biofilm Formation and Virulence - Kim, Yong-Guy; Lee, Jin-Hyung; Raorane, Chaitany J.; Oh, Seong T.; Park, Jae G.; Lee, Jintae (Frontiers in Microbiology, 2018)
Staphylococcus aureus is notorious for its ability to become resistant to antibiotics and biofilms play a critical role in antibiotic tolerance. S. aureus is also capable of secreting several exotoxins associated with the pathogenesis of sepsis and pneumonia. Thus, the objectives of the study were to examine S. aureus biofilm formation in vitro, and the effects of herring oil and its main components, omega fatty acids (cis-4,7,10,13,16,19-docosahexaenoic acid (DHA) and cis-5,8,11,14,17-eicosapentaenoic acid (EPA)), on virulence factor production and transcriptional changes in S. aureus. Herring oil decreased biofilm formation by two S. aureus strains. GC-MS analysis revealed the presence of several polyunsaturated fatty acids in herring oil, and of these, two omega-3 fatty acids, DHA and EPA, significantly inhibited S. aureus biofilm formation. In addition, herring oil, DHA, and EPA at 20 μg/ml significantly decreased the hemolytic effect of S. aureus on human red blood cells, and when pre-treated to S. aureus, the bacterium was more easily killed by human whole blood. Transcriptional analysis showed that herring oil, DHA, and EPA repressed the expression of the α-hemolysin hla gene. Furthermore, in a C. elegans nematode model, all three prolonged nematode survival in the presence of S. aureus. These findings suggest that herring oil, DHA, and EPA are potentially useful for controlling persistent S. aureus infection.